The Effect of Postpartum Exercises on Uterine Involution in Postpartum Mothers in Sei Serindan Village, Sei Kepayang Barat District, Asahan Regency - Pohan, Rostina Afrida (International Journal of Public Health Excellence (IJPHE), 2023)
Uterine involution is the process of the uterus returning to its pre-pregnancy shape. Postpartum exercise is a form of muscle training and is very good for postpartum mothers. The shrinkage of the first parity post partum uterus was faster than the second parity post partum in mothers in Sei Serindan village, Sei Kepayang Barat sub-district. The research method is quasi-experimental with pre-test and post-test design. The population of this study was 30 postpartum mothers who gave birth in Sei Serindan Village, West Sei Kepayang District from February to June 2023. The sample size was 30 people using the total sampling technique. Statistical analysis with Independent T test. The results of the study were uterine involution of postpartum women who did not exercise, the average height on the seventh day was 6.93 cm, on the twelfth day the average height was 3.00 cm. Uterine involution of postpartum mothers who did exercise on the seventh day was 4.73 cm high on the seventh day, and 0.33 cm on the twelfth day. There is an effect of postpartum exercise on uterine involution of postpartum mothers with independent t test values ​​with sig: 0.000 <0.05. There is a difference in the effect of mothers who do postpartum exercise and those who do not exercise with a decrease in uterine involution of 2,200 cm on the seventh day and 2,267 cm on the twelfth day. The conclusion of the study is that there is an effect of postpartum exercise on uterine involution of postpartum mothers.